Da competência comunicativa à lingüístico-discursiva : implicações para o ensino e aprendizagem de língua estrangeira - Stefanello, Carla Marli Adiers (2007)
The present study investigates theoretician-practical repercussions of the evolution from communicative competence into linguistic-discursive, occurred by socio-interactive of language , humanistic and socio-cultural of education conceptions in the teaching and learning English as a foreign language. This study is an exploratory descriptive bibliographical research. The produced data had been argued in accordance with the analytical reading method, based into the ideal proposed by Vygotsky and Bakhtin, because their ideas were in agreement with the subject matters presented in this study. Through the ideas presented in this paper was realized an analysis of the theoretician-practical English teaching on social-political, theoretician-pedagogy, didactic-methodological from the communicative approach aspects . From understanding and interpretation of these data was possible to show the socio-interactive conception implications, still tenuous, in the theoretician-practical samples experience of teaching and learning English as a foreign language, in the last decade. The teaching practices are still permeable, above all in the formal school, by language and education traditional conceptions